Glutamate receptors in the medial geniculate nucleus are necessary for expression and extinction of conditioned fear in rats - Orsini, Caitlin A. (2009)
Auditory fear conditioning requires anatomical projections from the medial geniculate nucleus (MGN) of the thalamus to the amygdala. Several lines of work indicate that the MGN is a critical sensory relay for auditory information during conditioning, but is not itself involved in the encoding of long-term fear memories. In the present experiments, we examined whether the MGN plays a similar role in the extinction of conditioned fear. Twenty-four hours after Pavlovian fear conditioning, rats received bilateral intrathalamic infusions of either with NBQX (an AMPA receptor antagonist; Experiment 1) or MK-801 (an NMDA receptor antagonist; Experiment 1), anisomycin (a protein synthesis inhibitor; Experiment 2) or U0126 (a MEK inhibitor; Experiment 3) immediately prior to an extinction session in a novel context. The next day rats received a tone test in a drug-free state to assess their extinction memory; freezing served as an index of fear. Glutamate receptor antagonism prevented both the expression and extinction of conditioned fear. In contrast, neither anisomycin nor U0126 affected extinction. These results suggest that the MGN is a critical sensory relay for auditory information during extinction training, but is not itself a site of plasticity underlying the formation of the extinction memory.